SAMAMBAIAS E LICÓFITAS DO PARQUE ESTADUAL DO MIRADOR, NORDESTE, CERRADO BRASILEIRO: Estudo florístico e sinopse de Thelypteridaceae para o estado do Maranhão, Brasil - OLIVEIRA, Sirlane Santos (2024)
The Mirador State Park (PEM), located in the state of Maranhão, encompasses an area of 766,781.00 hectares and includes in its almost all typical vegetation formations that compose the Cerrado domain. Furthermore, it is recognized as the second largest Conservation Unit of the Cerrado and the largest Integral Protection Unit of Maranhão. This work presents a floristic inventory, with descriptions and taxonomic comments, identification keys and information on the geographical distribution, environments of occurrence and Conservation Status of the species of ferns and lycophytes occurring in Mirador State Park, Brazilian Cerrado. In addition, it discusses the importance of this area in the state and provides a synopsis for Thelypteridaceae, one of the most diverse fern families in Maranhão. The collection of botanical material in PEM was conducted in three expeditions, in february and june 2023, and in january 2024. The specimens were collected following usual techniques for taxonomic groups. The synopsis of Thelypteridaceae was based on works already published for Maranhão, on material deposited in herbaria, and new field excursions in the state. The inventory of ferns and lycophytes carried out for the PEM recorded 29 species distributed in 20 genera and 15 families. Lycophytes are represented by five species, genera, and two families, while ferns consist on 24 species, 16 genera, and 13 families. The most representative families in terms of number of species were Pteridaceae and Lycopodiaceae, with four species each. The genera with the greatest richness were Adiantum and Lindsaea, with three species each. The terrestrial life form was predominant among the species collected. The types of phytophysiognomies with the highest species richness were gallery forest (15 spp.) and vereda (4 spp.). Fifteen species of Thelypteridaceae are treated for the state of Maranhão, with the greatest richness recorded for the genus Meniscium. Among the 15 species, Meniscium longifolium Desv. is a new record for the state flora.